Art Cologne 1990. - Galerie Neher, Essen; Art Cologne 1990 (Essen : Galerie Neher, 1990)
Arp, hans (Jean) ; Ackermann, Max ; Götz, Karl Otto ; Baumeister, Willi ; Winter, Fritz ; Kricke, Norbert ; Schultze, Bernard ; Luther, Adolf ; Thieler, Fred ; Mack, Heinz ; Piene, Otto ; Graubner, Gotthard ; Uecker, Günther ; Richter, Gerhard ; Nay, Ernst Wilhelm ; Warhol, Andy ; etc.
Art Cologne 1990, Art Cologne (Köln Messe), 15. bis 21. November 1990 - Stand Galerie Neher, Essen
boek